AB0260 Flares of Disease Activity as Risk Factor for Myocardial Infarction in Patients with Rheumatoid Arthritis. (9th June 2015) - Bakker, E.A.; Geuijen, P.M.; Radovits, B.J.; Arts, E.E.; den Broeder, A.A.; Popa, C.D.; Fransen, J.
Abstract : Background: Rheumatoid arthritis (RA) patients have an increased risk of cardiovascular diseases (CVD). A higher average level of disease activity in RA patients might cause MI, however this association was not confirmed (1). A relevant risk factor for MI might be flares; temporary exacerbations of disease activity. Objectives: To determine whether annual flare rate is associated with the occurrence of MI in RA patients. Methods: We employed a nested case-control design in a large Dutch prospective RA inception cohort, which started in 1985. Medical files and death certificates of RA patients were used to determine the occurrence of MI events. Patients were defined as cases when they experienced a MI event (physician diagnosis and checked in the records) after diagnosis of RA and within the observation period. Controls consisted of RA patients (ratio 4:1) matched on disease duration: the time between RA diagnosis and MI event or censoring. Flares were defined as an increase in DAS28>1.2 or >0.6 if DAS28≥3.2 (2). The annual flare rate was calculated as the number of flares divided by disease duration. Other important characteristics of RA and risk factors for CVD were determined at baseline or during follow-up. Characteristics of cases and controls were compared by unpaired t-tests or Mann-Whitney U. Logistic regression was performed to determine the crude association between the annual flare rate and occurrence of MI. Confounding variables were taken into account in multivariate logistic regression. Variables were identified as confounders if their inclusion in the model changed the coefficient (B) of annual flare rate with ≥10%. Results: The study population consisted of 41 cases and 181 matched controls. The proportion of men differed significantly between cases (51%) and controls (31%). Mean age at MI event was significantly higher than age at censoring. Furthermore, risk factors for CVD were raised in cases, like significantly higher BMI, total cholesterol, triglyceride, LDL, atherogenic index, incidence of hypertension and, a significantly lower HDL, compared to controls. Other characteristics like smoking status, disease duration, average DAS28, rheumatoid factor, C-reactive protein, incidence of diabetes mellitus and medication use did not differ significantly between cases and controls. The crude OR of the annual flare rate and the occurrence of MI was 0.78 (95% CI: 0.48; 1.25). The OR adjusted for age, LDL, male gender, cholesterol, hypertension, and HDL was 0.97 (95% CI: 0.58; 1.68). Conclusions: In contrast to expectations, no significant association was found between annual flare rate and the occurrence of MI in RA patients. This suggests that there is no large influence of flares in disease activity on incidence of MI in RA patients. Limitations that might cause bias include issues in definition of flare, and limited precision. References: Radovits BJ, Popa-Diaconu DA, Popa C, Eijsbouts A, Laan RF, van Riel PL, et al. Disease activity as a risk factor for myocardial infarction in rheumatoid arthritis. Annals of the rheumatic diseases. 2009;68(8):1271-6. van der Maas A, Lie E, Christensen R, Choy E, de Man YA, van Riel P, Woodworth T, den Broeder AA. Construct and criterion validity of several proposed DAS28-based rheumatoid arthritis flare criteria: an OMERACT cohort validation study. Ann Rheum Dis. 2013 Nov;72(11):1800-5. Disclosure of Interest: None declared